Legume (Mucuna pruriens)-cereal products in livestock fattening rations: IPSR Innovation Profile - Manyawu, Godfrey J.; Gwiriri, Lovemore C.; Chakoma, Irenie; Moyo, Siboniso; Dube, Sikhalazo; Murungweni, Chrispen; Maarsdorp, Barbara; Mashanda, Promise; Chakoma, Charles (CGIAR System Organization, 2022)
This innovation involves incorporation of coarsely-ground Mucuna pruriens grain as a unique, cost-effective ingredient and energy-protein dense substitute in maintenance or fattening rations of ruminant livestock, where standard commercial supplements would usually contain a combination of cereal grains (e.g., maize) and legume oil cakes (e.g., Soyabean, cotton seed etc), which are themselves generally expensive. These expensive ingredients make the commercial concentrates out of reach for most farmers. In contrast, Mucuna is cheaper and provides both energy and protein in one grain. Once ground, the Mucuna meal will be constituted together with home-made tropical forage legumes (e.g., Lablab purpureus) hay to make a complete diet which smallholder farmers can brand and trade among themselves. Incorporation of legume hay reduces the amount of poor-quality grass hay and cereal crop residues that will be included as basal forage in the complete diet and will simultaneously improve the digestibility of the poor-quality residues, leading to improved animal growth.